Association of adenovirus 36 and gynecomastia development: A case-control study (Annals of Medical Research, 2021)
Aim: The interaction of various adipokines secreted from adipose tissue during Adenovirus 36 (Ad-36) infection may cause gynecomastia. In this study, we aimed to evaluate the association between Ad-36 and gynecomastia development by determining DNAs and antibodies of Ad-36, adiponectin, leptin, and IL-6 levels.Materials and Methods: Patient and control groups were composed of from 33 male adults with gynecomastia and 15 male adults with anatomic disorders without gynecomastia, respectively. Serum neutralization assay (SNA) was used for the determination of Ad-36 antibodies and PCR method was used for the determination of Ad-36 DNA.Results: No Ad-36 DNA was found in the breast tissue samples. Ad-36 antibody levels were detected in the patient group with gynecomastia higher than the control group (p0.05). Serum leptin and adiponectin levels were detected to be significantly different from each other (p0.05).Conclusion: In conclusion, a low-grade chronic inflammation may be caused by Ad-36 infections, leading to increased circulating leptin levels. Consequently, leptin may lead to an increase in local or circulating estrogen levels by stimulating the aromatase enzyme in breast tissue and adipose stromal cells.